Sustained Attention Performance during Sleep Deprivation Associates with Instability in Behavior and Physiologic Measures at Baseline - Chua, Eric Chern-Pin (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: To identify baseline behavioral and physiologic markers that associate with individual differences in sustained attention during sleep deprivation. DESIGN: In a retrospective study, ocular, electrocardiogram, and electroencephalogram (EEG) measures were compared in subjects who were characterized as resilient (n = 15) or vulnerable (n = 15) to the effects of total sleep deprivation on sustained attention. SETTING: Chronobiology and Sleep Laboratory, Duke-NUS Graduate Medical School Singapore. PARTICIPANTS: Healthy volunteers aged 22-32 years from the general population. INTERVENTIONS: Subjects were kept awake for at least 26 hours under constant environmental conditions. Every 2 hours, sustained attention was assessed using a 10-minute psychomotor vigilance task (PVT). MEASUREMENTS AND RESULTS: During baseline sleep and recovery sleep, EEG slow wave activity was similar in resilient versus vulnerable subjects, suggesting that individual differences in vulnerability to sleep loss were not related to differences in homeostatic sleep regulation. Rather, irrespective of time elapsed since wake, subjects who were vulnerable to sleep deprivation exhibited slower and more variable PVT response times, lower and more variable heart rate, and higher and more variable EEG spectral power in the theta frequency band (6.0-7.5 Hz). CONCLUSIONS: Performance decrements in sustained attention during sleep deprivation associate with instability in behavioral and physiologic measures at baseline. Small individual differences in sustained attention that are present at baseline are amplified during prolonged wakefulness, thus contributing to large between-subjects differences in performance and sleepiness. CITATION: Chua EC; Yeo SC; Lee IT; Tan LC; Lau P; Cai S; Zhang X; Puvanendran K; Gooley JJ. Sustained attention performance during sleep deprivation associates with instability in behavior and physiologic measures at baseline. SLEEP 2014;37(1):27-39.